On the theoretical framework for meniscus-guided manufacturing of large-area OPV modules - Gumpert, Fabian; Janßen, Annika; Basu, Robin; Brabec, Christoph; Egelhaaf, Hans-Joachim; Lohbreier, Jan; Distler, Andreas (Progress in Organic Coatings, 2024)
For the manufacturing of thin films of solution-processable organic semiconductors, e.g. for organic photovoltaics (OPV), meniscus guided-coating techniques are the method of choice for large-scale industrial applications. However, the process requires an in-depth understanding of the respective fluid dynamics to control the resulting film thickness. In this article, we derive an analytical expression to describe the layer thickness of coatings manufactured with a trapezoidal-shaped applicator as a function of various fluid and process parameters. The analytical calculations are compared with results from computational fluid dynamics (CFD) simulations and experimental data for an industrially relevant OPV active material system. The good agreement of all three approaches demonstrates the potential of the analytical and simulative methods to minimize the number of time- and resource-consuming experiments. Furthermore, our theoretical model can be used to enhance the homogeneity of large-area coatings by means of an acceleration profile of the applicator that can compensate for the liquid loss during the coating process. The respective analytical expression is validated by simulated and experimentally obtained data for long-distance coatings. Finally, this approach is used to fabricate a large-area OPV module with new world record efficiency.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Accelerated coating velocity; Analytical description; Computational fluid dynamics; Meniscus-guided coating; Organic photovoltaics; Thin films